Assessment of Thevetia neriifolia Juss. Toxicity as a Rodenticide in Wistar Rats - Fayinminnu, Olajumoke O.; Adebiyi, Funmilayo G.; Fashola, Ebunoluwa I.; Gbemibade, Temitayo A.; Ogunwole, Olugbenga A. (Journal of Agricultural Studies, 2022)
Problems of rodents cannot be over underlined as a household and agricultural pest, damaging the crops on the field and stored produce thereby reducing qualities of produce. Controlling rodents using physical, biological and chemical methods have resulted in a slow rate success, several dangers on humans, animals and environment, hence they are discouraged. Thevetia neriifolia has been found to be a rich source of pesticide substance that could be used in crop protection; thus, its powdered form could be used as a baseline for potential natural rodenticide bait. The rodenticide capability of Thevetia neriifolia was evaluated using 50 female Wistar rats weighing 80±10 g which were acclimatized for seven days. The rats were allotted to ten treatments, each replicated five times. There was a Standard Reference Feed (diet) (SRF). The test samples were milled (with 2 mm sieve) sun-dried seed (SS), sun-dried leaf (SL) and sun-dried stem bark (SB). Each sample was incorporated at 15%, 30% and 45% into the reference diets. The allotments were in a completely randomized design. Experimental rats were fed with separate diets and supplied water ad-libitum for seven days. Results showed significant differences (p<0.05) in all the parameters. Rats on SS and SB at 45% inclusion levels had the lowest body weight reduction. Also, the lowest feed intake was observed in rats fed 45% SS, while those on 15% SL and SRF had the highest feed intake. Packed cell volume and hemoglobin were the only hematological parameters that differed significantly (p<0.05) at 15% and 45% SL inclusion levels. The serum biochemical parameters were not affected by the treatments (p>0.05). Organ sections (livers, hearts and kidneys) showed moderate congestion of sinusoids, multiple foci of mononuclear cells and congestion of renal blood vessels of rats on 45% SS inclusion level. No mortality or abnormal behavioural changes were observed among animals on SRF. Varying dietary inclusion levels of test samples resulted in rat mortalities which was attributed to cardiac glycosides. Rats on 45% SS died faster within 96 hours than those on corresponding inclusion levels of SB and SL which died after 216 hours. Therefore, Thevetia neriifolia has rodenticide capability and could be used as baits for rats.